Development and evaluation of a polymerase chain reaction assay to detect Bovine herpesvirus 1 - Rodríguez Medina, M.; Avila Sánchez, M.; Díaz de Arce Landa, H.; Barrera Valle, M. (Spanish Journal of Agricultural Research, 2009)
A polymerase chain reaction (PCR) assay to detect Bovine herpesvirus 1 (BoHV-1) has been developed and evaluated. This assay was based on the amplification of a viral thymidine kinase (tk) gene fragment, for which a novel pair of primers and different PCR conditions were tested. Under optimal conditions, no amplification was observed from heterologous herpesviruses or other bovine viruses. However, a 202 bp band from BoHV-1 was obtained confirming the specificity of the assay. An analytical sensitivity of 0.15 TCID50 per reaction led to the detection of BoHV-1 in nasal swab supernatants up to 11 days after experimental infection of cattle. There was a 100% match on the results until six days post-infection when PCR was compared with virus isolation and fluorescent antibody test (FAT). Starting the seven day post-infection and until the end of the experiment most of the positive samples were obtained by PCR. This simple PCR strategy do not use co-solvents in order to eliminate non-specific products or increase the efficiency of the amplification, provides a rapid method for diagnosis of BoHV-1 diseases in contrast with semi-nested or nested protocols with more time-consuming and a higher contamination rate, moreover, can be easily used in all diagnosis laboratories.